Long-lasting Effects of Minocycline on Behavior in Young but not Adult Fragile X Mice - Dansie, Lorraine E. (2013)
Fragile X Syndrome (FXS) is the most common single-gene inherited form of intellectual disability with behaviors characteristic of autism. People with FXS display childhood seizures, hyperactivity, anxiety, developmental delay, attention deficits, and visual-spatial memory impairment, as well as a propensity for obsessive-compulsive disorder (OCD). Several of these aberrant behaviors and FXS-associated synaptic irregularities also occur in “fragile X mental retardation gene” knock-out (Fmr1 KO) mice. We previously reported that minocycline promotes the maturation of dendritic spines - postsynaptic sites for excitatory synapses - in the developing hippocampus of Fmr1 KO mice, which may underlie the beneficial effects of minocycline on anxiolytic behavior in young Fmr1 KO mice. In this study, we compared the effectiveness of minocycline treatment in young and adult Fmr1 KO mice, and determined the dependence of behavioral improvements on short-term versus long-term minocycline administration. We found that 4 and 8 week long treatments significantly reduced locomotor activity in both young and adult Fmr1 KO mice. Some behavioral improvements persisted in young mice post-treatment, but in adults the beneficial effects were lost soon after minocycline treatment was stopped. We also show, for the first time, that minocycline treatment partially attenuates the number and severity of audiogenic seizures in Fmr1 KO mice. This report provides further evidence that minocycline treatment has immediate and long-lasting benefits on FXS-associated behaviors in the Fmr1 KO mouse model.